Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
Must add: 202
Step-by-step explanation:
[tex]The \ formula \ for \ perfect \ square => (a + b)^2 = a^2 + 2ab + b^2[/tex]
a = x
2ab = 26x
2ab = 26a [ substitute a instead of x]
[tex]b = \frac{26a}{2a}[/tex]
b= 13
So,
[tex](x + 13)^2 = x^2 + 26x + 169[/tex]
But given equation is :
[tex]x^2 + 26x = 33\ => \ x^2 + 26x -33 = 0[/tex]
We have find the difference between 169 and -33 to get the number that should be added to get the perfect square.
That is , 169 - (-33) = 202
Therefore ,
[tex]x^2 + 26x -33 + 202 \ makes \ given \ equation \ a \ perfect \ square[/tex]
- x²+26x=33
Multiply by 4a
- 4x²+104x=132
- (2x)²+2(2x)(21)=132
21²=441 must be added to get complete square
Remark
You can also add 13² =169 as 2(13)(x)=26x
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.